1977
DOI: 10.1111/j.1469-8986.1977.tb02972.x
|View full text |Cite
|
Sign up to set email alerts
|

Classical Skin Conductance Response Conditioning: Effects of Random Intermittent Reinforcement

Abstract: To assess some implications of incremental‐decremental learning theories for classical conditioning, skin conductance response conditioning in humans was examined as a function of reinforcement schedule. First anticipatory responses (FARs: latency from 1.0 to 3.5 sec after signal onset) were not affected by reinforcement ratio, but, during the first half of training, the probability of second anticipatory responses (SARs: latency from 3.6 to 7.0 sec after signal onset) increased with increases in reinforcement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 16 publications
1
9
1
Order By: Relevance
“…There was no significant difference between negative and positive runs in McAndrew et al (2012), and the data reported by Williams and Prokasy (1977) went descriptively in the wrong direction (note, however, that the procedure and notably the reinforcement rate, were different). The only result clearly in line with the Perruchet Length and Type of the Preceding Run Figure 5.…”
Section: Fear Conditioningcontrasting
confidence: 55%
See 1 more Smart Citation
“…There was no significant difference between negative and positive runs in McAndrew et al (2012), and the data reported by Williams and Prokasy (1977) went descriptively in the wrong direction (note, however, that the procedure and notably the reinforcement rate, were different). The only result clearly in line with the Perruchet Length and Type of the Preceding Run Figure 5.…”
Section: Fear Conditioningcontrasting
confidence: 55%
“…This means that, when all the condi tions are considered, there was evidence neither for the monotonic increase from the long runs of CS-alone to the long runs of CS-US that is predicted by associative strength theory, nor for the mono tonic decrease predicted by expectancy theory. McAndrew et al (2012) briefly mention in their discussion that an earlier study by Williams and Prokasy (1977) reported different results. Indeed, Williams and Prokasy concluded that the proba bility of galvanic responses in a partial reinforcement paradigm "decreases across sequences of successively reinforced trials and increased across sequences of successively nonreinforced trials" (their abstract).…”
Section: Fear Conditioningmentioning
confidence: 94%
“…Another piece of converging evidence comes from a recent electrodermal conditioning study in which a tone was followed by an aversive burst of white noise in 50% of the trials in the experimental condition but not in the control condition in which all the trials were reinforced (Perruchet, Grégoire, Aerts, & Poulin-Charronnat, 2016). Perruchet et al (2016) observed that, as in previous electrodermal conditioning studies (McAndrew, Jones, McLaren, & McLaren, 2012; Williams & Prokasy, 1977), the conditioned electrodermal responses tended to follow expectancies and conformed to the gambler fallacy rather than to the strength of the association between the two stimuli—suggesting that expectancies prevail over strength in this task. However, when the effect of the associative strength was isolated by subtracting the slope of the control participants (therefore controlling for response habituation), performance followed the linear trend predicted by variations in associative strength, as observed in all the other paradigms using the Perruchet procedure.…”
Section: Discussionsupporting
confidence: 70%
“…At this point we have to acknowledge that there are some contradictory findings in the literature with respect to our result. Williams and Prokasy (1977) in particular looked at electrodermal conditioning and found that, far from the SCR change increasing with level while expectancy declined, both SCR change and expectancy declined with level giving a positive correlation between the two. There are many possible reasons for this discrepancy between the two sets of results, however, as they used a loud noise as the US, did not measure the SCR in anything like the same way (and when they considered measures more like ours they found no reliable effect), and their procedures (e.g., control of run length) varied a great deal from ours.…”
Section: Discussionmentioning
confidence: 99%